The Effect of Avena sativa L. Cream on Acute Radiation Dermatitis in Breast Cancer Patients: Avena. sativa Cream on Skin Problems due to Radiotherapy - Antikchi, Mahnaz; Ghiyasvandian, Shahrzad; Farnia, Farahnaz; Shabani, Masood; Kamalinejad, Mohammad (Iranian Journal of Pharmaceutical Sciences, 2023)
Based on estimates, the skin reactions caused by radiation therapy in women with breast cancer range from 87 to 96%. Since the purpose of complementary and alternative medicine in nursing care is to alleviate suffering and increase patient comfort, the researchers decided to evaluate the medicinal properties of Avena sativa L. and the effectiveness of Avena sativa L. cream on skin problems caused by radiation therapy in women with breast cancer. In this clinical trial, 66 patients with breast cancer were divided into two groups: the intervention and the control group. From the beginning to the end of the radiation therapy, the Intervention group was treated with creams containing extracts of Avena sativa L. applied locally and three times a day, and the control group used cream lacking Avena sativa L. extract. The degree of skin problems, erythema, and dry and moist desquamation in the special intervals in both groups were evaluated. The study results revealed no significant difference in the degree of radio dermatitis in both groups. However, clinically, the incidence of dry desquamation in the intervention group is lower than in the control group but statistically insignificant. There was no significant difference between the two groups with moist desquamation and mild and bright erythema incidence. Conclusion: The results showed that local products made with Avena sativa L. extract can be used in radiation-induced skin reactions such as dry desquamation, and it is very effective. Therefore, further studies with larger sample sizes are recommended to prove this.